THE STATE OF NIGERIAN ECONOMY IN THE 21ST CENTURY; PRIVATIZATION AND COMMERCIALIZATION PROGRAMMES UNDER OBASANJO/ATIKU REGIME - Kabir Mohammed; David Chapola; Ashiru Bello (European Scientific Journal, ESJ, 2013)
The inappropriate privatization and commercialization of the Nigerian public corporations under Obasanjo/Atiku regime is one of the major economic obstacles responsible for the decline of our national economy. The study justifies that the Nigerian public sectors were unjustly and improperly privatized and commercialized aimed at satisfying the political, economic and social interests of the authority concerned. In view of the current economic hardship and other problems associated with privatization, the study calls for revisitation of the already commercialized public sectors for the betterment, economic growth and development of our beloved country. It further argues that the strategies adopted while privatizing public utilities were inappropriate, unjust and insignificant to the economic life of the deluded Nigerian masses. At the tail end, the study proffers ways forward, among others include; good governance, resource control, management and efficiency.